Summer Fridays : a novel - Rindell, Suzanne (Dutton, an imprint of Penguin Random House LLC, 2024)
"Summer of 1999: Twenty-something Sawyer is balancing a new city, her suddenly-distant fiancée, her assistant job in publishing, and making a mark with her own writing. When she meets Nick, boyfriend to her fiancee's all-too-close female colleague-seriously, since when is karaoke part of staying late to work on a case?-Sawyer's lonely summer in New York takes an unexpected turn. At first she finds Nick salty and smug, and he finds Sawyer stuck in her own head. When Nick seeks out Sawyer online to apologize for said saltiness and smugness - the early days of AOL and instant messenger banter ensue - a friendship develops. As their relationship evolves, and Sawyer finds herself increasingly alone in her hot apartment, she and Nick begin an unofficial ritual-exploring New York City every "Summer Friday". From hot dogs on the Staten Island Ferry and Sea Breezes in a muggy East Village bar to swimming at Coney Island, Sawyer feels seen by Nick in a way that surprises her. He pushes her to be braver. To ask for what she wants. To follow her secret dream to write, and to advocate for herself at work. She pushes him to open up. To tell her what he's really thinking about things. At the end of the summer, with her wedding date looming large, Sawyer must choose between the life she thought she was living, and the freedom and joy she feels with Nick"--